Population-genetic research of the VDR gene polymorphism - A. N. Volkov; E. V. Tsurkan (Фундаментальная и клиническая медицина)
Aim. To explore the prevalence of alleles and genotypes in rsl544410 polymorphism within the VDR gene in the population of Kemerovo Region.Materials and Methods. Genotyping was performed in 232 residents of Kemerovo region (125 men and 107 women, average 58,3 ± 1,86 (range 45-74) years of age). DNA was extracted from the peripheral blood utilizing a thermocoagulation method while genotyping was carried out by allele-specific polymerase chain reaction.Results. Heterozygous (G/A)    rsl544410 genotype prevailed in the studied sample (46.1%). Homozygous genotype A/A associated with the reduced bone mineral density and osteopenia/osteoporosis was defined in 13.8% of individuals. The ratio of rsl544410 genotypes was comparable with that of ethnically close populations.Conclusion. High population frequency of the A/A genotype of the rsl544410 polymorphism within the VDR gene may be one of the factors determining the high prevalence of osteoporosis in the population of Kemerovo Region.